(untitled) (Journal of Information Technologies in Education (ITE), 2010)
In the article the problem of application of information-communication technologies during the course of advanced training by the teachers of pre-school educational establishments and by the teachers of elementary school are analyzed. The possibilities of in-service teacher education in this process are considered.